Impacts of Pre-bloom Leaf Removal on Wine Grape Production and Quality Parameters: A Systematic Review and Meta-Analysis - VanderWeide, Joshua; Gottschalk, Chris; Schultze, Steven R.; Nasrollahiazar, Esmaeil; Poni, Stefano; Sabbatini, Paolo (Frontiers in Plant Science, 2021)
Wine grape (Vitis vinifera L.) is the most widely cultivated fruit crop in the world. However, the climactic characteristics in some growing regions are suboptimal for grape production, including short season length and excess precipitation. Grape growers can utilize an array of methods to mitigate these issues, including “early leaf removal,” a management practice involving the removal of leaves from selected basal nodes along shoots around bloom. This meta-analysis reviews the extensive literature on this practice, with specific regards to application at “pre-bloom” (PB). 175 publications on the topic of “early leaf removal” were identified using key terms, and subsequently narrowed via eight data curation steps. The comparison between treated (PB) and control plants in these studies revealed two important results. First, PB lowered bunch rot disease (-61%), partially through reducing the compactness of clusters. Second, PB promoted a significant increase in fruit total soluble solids (°Brix, +5.2%), which was related to the increase in the leaf-to-fruit ratio. Furthermore, cultivar and rootstock were found to have a large influence on the success of PB, while the contribution of climate was smaller. In conclusion, PB significantly lowers bunch rot disease and increases °Brix, both of which improve grape and wine quality.